Phosphorus-nitrogen double-doped high-capacity resin-based hard carbon negative electrode material and preparation method thereof

By synthesizing resin precursor materials containing phosphorus and nitrogen elements and preparing double-doped hard carbon materials with phosphorus and nitrogen by pyrolysis, the problems of low lithium storage capacity and poor rate performance of hard carbon negative electrode materials are solved, and the performance of lithium-ion batteries with high energy density and long cycle life are achieved.

CN119503774AActive Publication Date: 2025-02-25CIVIL AVIATION FLIGHT UNIV OF CHINA

Patent Information

Application Number
CN202411902222.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-02-25
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing hard carbon negative electrode materials have low lithium storage capacity and poor rate performance, making it difficult to meet the needs of high energy density and long cycle life.

Method used

By synthesizing resin precursor materials containing phosphorus and nitrogen elements, and using pyrolysis method to prepare double-doped hard carbon materials containing phosphorus and nitrogen, to improve their specific capacity, cycle stability and rate performance.

Benefits of technology

It significantly improves the lithium storage capacity and cycle stability of hard carbon materials, and improves the energy density, rate performance and cycle life of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503774A_ABST
    Figure CN119503774A_ABST
Patent Text Reader

Abstract

The invention discloses a phosphorus-nitrogen-containing double-doped high-capacity resin-based hard carbon negative electrode material and a preparation method thereof, and the material is prepared by the following steps: reacting a nitrogen-containing organic matter 3-aminophenoxy phthalonitrile, which is independently and innovatively synthesized, with a phosphorus-containing organic matter 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO, so as to obtain the phosphorus-nitrogen-containing double-doped high-capacity resin-based hard carbon negative electrode material. And carrying out pyrolysis cross-linking and carbonization treatment on the precursor material to obtain the phosphorus-nitrogen double-doped resin-based hard carbon negative electrode material. The preparation method comprises the following steps: preparing a phosphorus-nitrogen double-doped resin-based precursor material, and preparing the phosphorus-nitrogen double-doped resin-based hard carbon negative electrode material. Through phosphorus-nitrogen double doping, the specific capacity, the cycling stability and the rate capability of the hard carbon material are effectively improved, and the problem that the theoretical capacity of a graphite negative electrode of a lithium ion battery is limited is solved; the prepared hard carbon negative electrode material has relatively high lithium ion storage capacity and excellent electrochemical performance, and is particularly suitable for a high-performance lithium ion battery; the preparation method of the material is simple and easy to implement, and has a good industrialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a phosphorus-nitrogen dual-doped high-capacity resin-based hard carbon negative electrode material and a preparation method thereof. Background Art

[0002] Since the 1980s, the research and development of lithium-ion batteries (LIBs) and their key materials has become a hot topic in the field of chemical energy storage. Compared with traditional secondary batteries, LIBs have the advantages of high energy density, long cycle life, light weight, and good safety. Therefore, they are widely used in portable electronic devices, electric vehicles, and renewable energy storage systems. Negative electrode materials play an important role in LIBs, and their performance directly affects the capacity, energy density, and safety of the battery. At present, graphite is widely used as a negative electrode material for commercial LIBs due to its good stability, but its theoretical specific capacity is only 372mAh / g, which is difficult to meet the demand for high energy density. As an amorphous carbon material with high specific capacity and good cycle performance, hard carbon has gradually become the research focus of the new generation of LIBs negative electrode materials.

[0003] Hard carbon is usually composed of a graphite-like microcrystalline structure and open angular microcrystals. This unique structure provides more lithium storage sites and can effectively alleviate the structural damage caused by volume expansion. However, the improvement of hard carbon performance is limited by the preparation method and precursor characteristics. In order to further optimize the electrochemical properties of hard carbon, researchers began to explore the use of heteroatom doping to enhance its conductivity and increase defect sites, thereby improving lithium storage capacity. In particular, the co-doping study of phosphorus and nitrogen has shown a significant effect on improving the capacity and cycle life of hard carbon.

[0004] The present invention synthesizes a special resin precursor material containing phosphorus and nitrogen elements and adopts a pyrolysis method to prepare a phosphorus-nitrogen dual-doped hard carbon material to solve the problems of low lithium storage capacity and poor rate performance of existing hard carbon negative electrode materials; and improves the energy density, rate performance and cycle life of lithium-ion batteries. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art, and to provide a high-capacity resin-based hard carbon negative electrode material containing phosphorus and nitrogen dual doping and a preparation method thereof. The material is prepared by reacting the independently innovatively synthesized nitrogen-containing organic 3-aminophenoxyphthalonitrile and the phosphorus-containing organic 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO to prepare a resin-based precursor material containing phosphorus and nitrogen dual doping, and the precursor material is subjected to pyrolysis, crosslinking and carbonization to obtain a phosphorus and nitrogen dual doped resin-based hard carbon negative electrode material. The present invention effectively improves the specific capacity, cycle stability and rate performance of the hard carbon material through phosphorus and nitrogen dual doping, and solves the problem of limited theoretical capacity of the graphite negative electrode of lithium ion batteries; the prepared hard carbon negative electrode material has a high lithium ion storage capacity and excellent electrochemical performance, and is particularly suitable for high-performance lithium ion batteries; the preparation method of the material is simple and easy, and has good industrialization prospects.

[0006] In order to achieve the above technical effects, the following technical solutions are adopted:

[0007] A method for preparing a phosphorus-nitrogen dual-doped high-capacity resin-based hard carbon negative electrode material, comprising:

[0008] Step S1: weighing nitrogen-containing organic matter and phosphorus-containing organic matter according to different doping ratios, mixing the nitrogen-containing organic matter and the phosphorus-containing organic matter in a solvent for reaction, heating the solution to react so as to precipitate a solid, washing and drying to obtain a phosphorus-nitrogen dual-doped resin-based precursor material;

[0009] Step S2: pyrolyzing the precursor material obtained in step S1 to cause a cross-linking reaction in the precursor material to obtain a cross-linked precursor material;

[0010] Step S3: placing the cross-linked precursor material obtained in step S2 under an inert gas protective atmosphere, controlling the heating rate and temperature, and carbonizing the cross-linked precursor material to obtain a high-capacity resin-based hard carbon material with different phosphorus and nitrogen doping ratios.

[0011] Step S4: placing the hard carbon material obtained in step S3 into a ball mill for ball milling, thereby preparing high-capacity resin-based hard carbon negative electrode materials with different phosphorus and nitrogen doping ratios;

[0012] The nitrogen-containing organic substance is 3-aminophenoxyphthalonitrile;

[0013] The phosphorus-containing organic matter is 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO.

[0014] Furthermore, in step S1, the mass ratio of nitrogen-containing organic matter to phosphorus-containing organic matter is 1-2:1-3.

[0015] Furthermore, the solvent in step S1 includes ethanol; the reaction temperature and precipitation temperature in step S1 are 70-90° C., and the reaction time is 4-6 hours.

[0016] Furthermore, the preparation method of the nitrogen-containing organic 3-aminophenoxyphthalonitrile in step S1 is:

[0017] 0.1-0.3 mol of 4-nitrophthalonitrile, 0.1-0.3 mol of 3-aminophenol and 0.12-0.24 mol of anhydrous potassium carbonate are mixed in 30-60 ml of dimethyl sulfoxide, refluxed at 80-90° C. for 8-10 hours under nitrogen protection, poured into distilled water after cooling to precipitate solid, and 3-aminophenoxyphthalonitrile is obtained through filtration and purification.

[0018] Furthermore, the specific preparation method of the phosphorus-nitrogen dual-doped resin-based precursor material in step S1 is:

[0019] 0.05-0.1 mol of 3-aminophenoxyphthalonitrile and 1.5-3 g of polyformaldehyde are mixed in 100-200 ml of ethanol, nitrogen is introduced, 0.05-0.15 mol of phosphorus-containing organic matter 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO and 5-10 ml of formic acid are added, the solution is heated to 70-90° C. and reacted for 4-6 hours to precipitate a yellow precipitate, which is washed and dried to obtain a phosphorus-nitrogen dual-doped resin-based precursor material.

[0020] Furthermore, the temperature rise program during the pyrolysis and cross-linking process in step S2 is:

[0021] The heating rate is 5-10℃ / min to 200-300℃, and the holding time is 4-6h.

[0022] Furthermore, the inert gas atmosphere in step S3 includes argon; the carbonization treatment container is a tubular furnace; and the temperature rise program during the carbonization treatment is:

[0023] The heating rate is 5-10℃ / min to 500-900℃, and the holding time is 2-4h.

[0024] Furthermore, the ball milling time in step S4 is 30-45 min.

[0025] A phosphorus-nitrogen dual-doped high-capacity resin-based hard carbon negative electrode material is prepared by the above preparation method.

[0026] Furthermore, the hard carbon negative electrode material is used in the graphite negative electrode of lithium-ion batteries.

[0027] The beneficial effects of the present invention are:

[0028] 1. The hard carbon negative electrode material of the present invention benefits from heteroatom doping. The nitrogen element component synthesized by independent innovation is introduced into the hard carbon material, thereby providing more reactive sites for the material and enhancing the electronic conductivity. The introduction of phosphorus increases the specific capacity of the material. The lithium storage capacity of the hard carbon material is significantly improved, thereby obtaining a high-capacity hard carbon negative electrode material; achieving a high specific capacity;

[0029] 2. The hard carbon negative electrode material of the present invention has good cycle stability. The material has strong cycle stability at high rates and is suitable for high-performance batteries;

[0030] 3. The hard carbon negative electrode material preparation method of the present invention is simple, uses common raw materials, has a simple and easy preparation process, and has the potential for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. The drawings in the following description are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.

[0032] Figure 1 This is an X-ray diffraction pattern of the material prepared at a carbonization temperature of 600° C. in Example 1 of the present invention;

[0033] Figure 2 The cyclic performance of the material prepared at a carbonization temperature of 600° C. in Example 1 of the present invention;

[0034] Figure 3 The rate performance of the material prepared at a carbonization temperature of 600° C. in Example 1 of the present invention;

[0035] Figure 4 This is an X-ray diffraction pattern of the material prepared at a carbonization temperature of 750° C. in Example 2 of the present invention;

[0036] Figure 5 The cyclic performance of the material prepared at a carbonization temperature of 750°C in Example 2 of the present invention;

[0037] Figure 6 The rate performance of the material prepared at a carbonization temperature of 750° C. in Example 2 of the present invention;

[0038] Figure 7 This is an X-ray diffraction pattern of the material prepared at a carbonization temperature of 900° C. in Example 3 of the present invention;

[0039] Figure 8 The cyclic performance of the material prepared at a carbonization temperature of 900° C. in Example 3 of the present invention;

[0040] Fig. 9 This is the rate performance of the material prepared at a carbonization temperature of 900°C in Example 3 of the present invention. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0042] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0043] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations and / or combinations thereof.

[0044] In the following examples, unless otherwise specified, all reagents and consumables were purchased from conventional reagent manufacturers in the field; unless otherwise specified, the experimental methods and technical means used were conventional methods and means in the field.

[0045] The phosphorus-nitrogen dual-doped high-capacity resin-based hard carbon negative electrode material and its performance provided by the present invention are described below in conjunction with the embodiments, and the protection scope of the present invention is not limited by the following embodiments.

[0046] Embodiment 1:

[0047] 1. Preparation of nitrogen-containing organic 3-aminophenoxyphthalonitrile

[0048] 0.1 mol of 4-nitrophthalonitrile, 0.1 mol of 3-aminophenol and 0.12 mol of anhydrous potassium carbonate were mixed in 30 ml of dimethyl sulfoxide, refluxed at 80° C. for 8 hours under nitrogen protection, cooled and poured into distilled water to precipitate a solid, which was filtered and purified to obtain 3-aminophenoxyphthalonitrile.

[0049] 2. Preparation of phosphorus-nitrogen dual-doped resin-based precursor materials

[0050] 0.05 mol of 3-aminophenoxyphthalonitrile and 1.5 g of polyformaldehyde were mixed in 100 ml of ethanol, nitrogen was introduced, 0.05 mol of phosphorus-containing organic matter 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO and 5 ml of formic acid were added, the solution was heated to 70°C and reacted for 4 hours, a yellow precipitate was precipitated, and after washing and drying, a phosphorus-nitrogen dual-doped resin-based precursor material PNP was obtained.

[0051] 3. Preparation of high-capacity resin-based hard carbon anode materials doped with phosphorus and nitrogen

[0052] 5 g of the prepared phosphorus-nitrogen dual-doped resin-based precursor material PNP powder was placed in a crucible, and the crucible was placed in a muffle furnace, and the temperature was raised to 200°C at a heating rate of 5°C / min, and the holding time was 4 hours to crosslink the material. The material was then transferred to a tube furnace, and the temperature was raised to 600°C at a heating rate of 5°C / min in an argon atmosphere, and the holding time was 2 hours. The carbonized material was taken out, and the mass was about 3.7 g.

[0053] 2 g of carbonized material was weighed and placed in a stainless steel ball mill, 20 g of stainless steel balls were weighed, and ball milling was performed for 30 min to obtain a high-capacity resin-based hard carbon anode material powder doped with phosphorus and nitrogen. Its XRD results are as follows: Figure 1 shown.

[0054] 4. Preparation of lithium-ion batteries

[0055] 70 wt% of phosphorus-nitrogen dual-doped high-capacity resin-based hard carbon anode material powder, 20 wt% of acetylene black and 10 wt% of sodium carboxymethyl cellulose (CMC) were stirred for 4 h to obtain a uniform slurry, which was then uniformly coated on a copper foil and dried at 60 ° C for 8 h. The electrode active material loading was 1.0-1.5 mg / cm 2 , the electrode thickness is about 15μm. The electrolyte uses 1.0M LiPF6 dissolved in ethylene carbonate (EC) and dimethyl carbonate (DMC), and the separator uses Celgard 2400 microporous polypropylene film. When assembling the battery, the negative electrode, positive electrode and separator are placed in the CR2032 button battery shell, injected with electrolyte and packaged.

[0056] The performance of lithium-ion batteries is tested, and the cycle performance is as follows: Figure 2 As shown in the figure, it can be seen that the specific capacity of the lithium-ion battery is stable at about 330mAh / g at a current density of 1A / g. After 1000 cycles, the capacity is still 230mAh / g. Its rate performance is as follows Figure 3 As shown, it can be seen that at a current density of 4A / g, there is still a specific capacity of 170mAh / g.

[0057] Embodiment 2:

[0058] The main difference between Example 2 and Example 1 is that the carbonization temperature of Example 2 is 750°C. The XRD pattern of the prepared material is as follows: Figure 4 shown.

[0059] The performance of lithium-ion batteries is tested, and the cycle performance is as follows: Figure 5 As shown in the figure, it can be seen that the specific capacity of the lithium-ion battery is stable at about 400mAh / g at a current density of 1A / g. After 1000 cycles, the capacity is still 340mAh / g. Its rate performance is as follows Figure 6 As shown, it can be seen that at a current density of 4A / g, there is still a specific capacity of 150mAh / g.

[0060] Embodiment 3:

[0061] The main difference between Example 3 and Example 1 is that the carbonization temperature of Example 3 is 900°C. Figure 7 shown.

[0062] The performance of lithium-ion batteries is tested, and the cycle performance is as follows: Figure 8 As shown in the figure, it can be seen that the specific capacity of the lithium-ion battery is stable at about 306mAh / g at a current density of 1A / g. After 1000 cycles, the capacity is still 350mAh / g. Its rate performance is as follows Fig. 9 As shown, it can be seen that at a current density of 4A / g, there is still a specific capacity of 198mAh / g.

[0063] Comparative Example 1:

[0064] Based on the preparation process of Example 1, 3-aminophenoxyphthalonitrile was replaced with 4-aminophenoxyphthalonitrile in this comparative example, and the other processes were consistent with Example 1.

[0065] 1. Preparation of nitrogen-containing organic matter 4-aminophenoxyphthalonitrile

[0066] 0.1 mol of 4-nitrophthalonitrile, 0.1 mol of 4-aminophenol and 0.12 mol of anhydrous potassium carbonate were mixed in 30 ml of dimethyl sulfoxide, refluxed at 80° C. for 8 hours under nitrogen protection, cooled and poured into distilled water to precipitate solids, which were filtered and purified to obtain 4-aminophenoxyphthalonitrile. The subsequent experimental steps were consistent with those in Example 1 of the present invention.

[0067] After replacing the nitrogen-containing organic matter, although the reaction process is similar, the ability and effect of reacting with DOPO are different. The battery performance of the final material is poor, and the material specific capacity and cycle stability are low. At a current density of 1A / g, the material's specific capacity is only 135mAh / g, and after 1000 cycles, the capacity is only 50mAh / g. It may be because 4-aminophenoxyphthalonitrile cannot react fully with DOPO, resulting in more structural defects in the material, affecting the conductivity and cycle performance of the battery.

[0068] Comparative Example 2:

[0069] Based on the preparation process of Example 1, the phosphorus-containing organic matter was replaced with 9-amino-10-phosphaphenanthrene in this comparative example, and the other processes were consistent with Example 1.

[0070] 2. Preparation of phosphorus-nitrogen dual-doped resin-based precursor materials

[0071] 0.05 mol of 3-aminophenoxyphthalonitrile and 1.5 g of paraformaldehyde were mixed in 100 ml of ethanol, nitrogen was introduced, 0.05 mol of phosphorus-containing organic matter (9-amino-10-phosphaphenanthrene) and 5 ml of formic acid were added, the solution was heated to 70 ° C for 4 hours, a yellow precipitate was precipitated, and a phosphorus-nitrogen dual-doped resin-based precursor material was obtained after washing and drying. The subsequent experimental steps are consistent with Example 1 of this patent.

[0072] Using 9-amino-10-phosphaphenanthrene instead of DOPO and reacting it with 3-aminophenoxyphthalonitrile, the resulting resin-based precursor material did not significantly improve battery performance. At a current density of 1A / g, the specific capacity of the material was only 189mAh / g, and after 1000 cycles, the capacity was only 140mAh / g. Although phosphorus-containing organic matter participated in the reaction, the phosphorus doping effect in the material was not ideal, resulting in poor battery capacity and cycle stability.

[0073] Comparative Example 3:

[0074] Based on the preparation process of Example 1, this comparative example does not perform a cross-linking step, and directly heats up for carbonization, and the other processes remain consistent with Example 1.

[0075] The phosphorus-nitrogen dual-doped resin-based precursor material is directly heated to 600°C in a nitrogen atmosphere at a heating rate of 5°C / min. No cross-linking step is performed, and the other experimental steps are consistent with Example 1 of this patent. Although the material that is directly carbonized and skips the cross-linking step has been carbonized, the lack of structural reinforcement during the cross-linking process results in a loose hard carbon structure, which greatly reduces the cycle stability of the battery. At a current density of 1A / g, although the initial specific capacity of the material reaches 430mAh / g, after 1000 cycles, the capacity is only 124mAh / g.

[0076] Comparative Example 4:

[0077] Based on the preparation process of Example 1, the crosslinking temperature of this comparative example was increased to 400° C., the time remained unchanged, and the other processes remained consistent with Example 1.

[0078] The phosphorus-nitrogen dual-doped resin-based precursor material is cross-linked at a cross-linking temperature of 400°C and then carbonized. The other experimental steps are consistent with Example 1 of this patent. Cross-linking is performed at 400°C. Although the cross-linking reaction can enhance the stability of the material, excessively high cross-linking temperature will cause the structure of the material to be too dense and the battery capacity to decrease. At a current density of 1A / g, the initial specific capacity of the material is only 230mAh / g. After 1000 cycles, the capacity is only 221mAh / g.

[0079] Comparative Example 5:

[0080] Based on the preparation process of Example 1, the crosslinking time of this comparative example was increased to 8 hours, the temperature remained unchanged, and the other processes remained consistent with Example 1.

[0081] The phosphorus-nitrogen dual-doped resin-based precursor material was cross-linked for 8 hours, followed by carbonization, and the other experimental steps were consistent with Example 1 of this patent. Although extending the cross-linking time helps to enhance the degree of cross-linking of the material, too long a cross-linking time may cause the material to be over-cross-linked, the structure to be too rigid, and the porosity to be reduced, which affects the battery's capacity and cycle stability, and exhibits poor battery performance. At a current density of 1A / g, the initial specific capacity of the material is only 268mAh / g, and after 1000 cycles, the capacity is only 155mAh / g.

[0082] Comparative Example 6:

[0083] Taking the preparation process of Example 1 as a benchmark, the carbonization heating rate of this comparative example is 50°C / min, the carbonization temperature is 600°C, and the other processes are consistent with Example 1.

[0084] The phosphorus-nitrogen dual-doped resin-based precursor material was carbonized at a heating rate of 50°C / min and a carbonization temperature of 600°C. The other experimental steps were consistent with Example 1 of this patent. Although increasing the carbonization heating rate may shorten the preparation time, it leads to incomplete formation of the material structure during the carbonization process, and the battery has poor capacity and stability. This may be due to the rapid heating that causes the unstable intermediate phase in the material to fail to fully transform. At a current density of 1A / g, the initial specific capacity of the material is only 244mAh / g, and after 1000 cycles, the capacity is only 157mAh / g.

[0085] Comparative Example 7:

[0086] Taking the preparation process of Example 1 as a benchmark, the crosslinking heating rate of this comparative example is 40°C / min, the crosslinking temperature remains unchanged, and the other processes remain consistent with Example 1.

[0087] The phosphorus-nitrogen dual-doped resin-based precursor material was cross-linked at a cross-linking heating rate of 40°C / min, followed by carbonization, and the other experimental steps were consistent with Example 1 of this patent. The high heating rate made the cross-linking process too fast, resulting in an uneven material structure, poor battery cycle stability, and low capacity. This may be due to the incomplete cross-linking reaction, which caused the pore structure of the hard carbon material to be unstable, thus affecting its battery performance. At a current density of 1A / g, the initial specific capacity of the material was only 235mAh / g, and after 1000 cycles, the capacity was only 171mAh / g.

[0088] In summary, the present invention discloses a high-capacity resin-based hard carbon negative electrode material containing dual doping of phosphorus and nitrogen and a preparation method thereof. The material is prepared by reacting the independently innovatively synthesized nitrogen-containing organic 3-aminophenoxyphthalonitrile and the phosphorus-containing organic 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO to prepare a resin-based precursor material containing dual doping of phosphorus and nitrogen, and the precursor material is subjected to pyrolysis, crosslinking and carbonization to obtain a phosphorus-nitrogen dual doped resin-based hard carbon negative electrode material. The present invention effectively improves the specific capacity, cycle stability and rate performance of the hard carbon material through dual doping of phosphorus and nitrogen, and solves the problem of limited theoretical capacity of graphite negative electrode of lithium-ion batteries; the prepared hard carbon negative electrode material has a high lithium ion storage capacity and excellent electrochemical performance, and is particularly suitable for high-performance lithium-ion batteries; the preparation method of the material is simple and easy, and has good industrialization prospects.

[0089] At this point, those skilled in the art recognize that, although the embodiments of the present invention have been shown and described in detail herein, many other variations or modifications that conform to the principles of the present invention can still be directly determined or derived based on the contents disclosed in the present invention without departing from the spirit and scope of the present invention. Therefore, the scope of the present invention should be understood and recognized as covering all such other variations or modifications.

Claims

1. A method for preparing a high-capacity resin-based hard carbon negative electrode material containing phosphorus and nitrogen dual doping, characterized in that: The preparation method comprises: Step S1: weighing nitrogen-containing organic matter and phosphorus-containing organic matter according to different doping ratios, mixing the nitrogen-containing organic matter and the phosphorus-containing organic matter in a solvent for reaction, heating the solution to react so as to precipitate a solid, washing and drying to obtain a phosphorus-nitrogen dual-doped resin-based precursor material; Step S2: pyrolyzing the precursor material obtained in step S1 to cause a cross-linking reaction in the precursor material to obtain a cross-linked precursor material; Step S3: placing the cross-linked precursor material obtained in step S2 under an inert gas protective atmosphere, controlling the heating rate and temperature, and carbonizing the cross-linked precursor material to obtain a high-capacity resin-based hard carbon material with different phosphorus and nitrogen doping ratios. Step S4: placing the hard carbon material obtained in step S3 into a ball mill for ball milling, thereby preparing high-capacity resin-based hard carbon negative electrode materials with different phosphorus and nitrogen doping ratios; The nitrogen-containing organic substance is 3-aminophenoxyphthalonitrile; The phosphorus-containing organic matter is 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO.

2. The method for preparing a high-capacity resin-based hard carbon negative electrode material containing phosphorus and nitrogen dual doping as claimed in claim 1, characterized in that: In step S1, the mass ratio of nitrogen-containing organic matter to phosphorus-containing organic matter is 1-2:1-3.

3. The method for preparing a high-capacity resin-based hard carbon negative electrode material containing phosphorus and nitrogen dual doping as claimed in claim 1, characterized in that: The solvent in step S1 includes ethanol; the reaction temperature and precipitation temperature in step S1 are 70-90° C., and the reaction time is 4-6 hours.

4. The method for preparing a high-capacity resin-based hard carbon negative electrode material containing phosphorus and nitrogen dual doping as claimed in claim 1, characterized in that: The preparation method of the nitrogen-containing organic substance 3-aminophenoxyphthalonitrile in step S1 is: 0.1-0.3 mol of 4-nitrophthalonitrile, 0.1-0.3 mol of 3-aminophenol and 0.12-0.24 mol of anhydrous potassium carbonate are mixed in 30-60 ml of dimethyl sulfoxide, refluxed at 80-90° C. for 8-10 hours under nitrogen protection, poured into distilled water after cooling to precipitate solid, and 3-aminophenoxyphthalonitrile is obtained through filtration and purification.

5. The method for preparing a high-capacity resin-based hard carbon negative electrode material containing phosphorus and nitrogen dual doping as claimed in claim 1, characterized in that: The specific preparation method of the phosphorus-nitrogen dual-doped resin-based precursor material in step S1 is: 0.05-0.1 mol of 3-aminophenoxyphthalonitrile and 1.5-3 g of polyformaldehyde are mixed in 100-200 ml of ethanol, nitrogen is introduced, 0.05-0.15 mol of phosphorus-containing organic matter 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO and 5-10 ml of formic acid are added, the solution is heated to 70-90° C. and reacted for 4-6 hours to precipitate a yellow precipitate, which is washed and dried to obtain a phosphorus-nitrogen dual-doped resin-based precursor material.

6. The method for preparing a high-capacity resin-based hard carbon negative electrode material containing phosphorus and nitrogen dual doping as claimed in claim 1, characterized in that: The temperature rise program during the pyrolysis and cross-linking process in step S2 is: The heating rate is 5-10℃ / min to 200-300℃, and the holding time is 4-6h.

7. The method for preparing a high-capacity resin-based hard carbon negative electrode material containing phosphorus and nitrogen dual doping as claimed in claim 1, characterized in that: The inert gas atmosphere in step S3 includes argon; the carbonization treatment container is a tubular furnace; the temperature rise program during the carbonization treatment is: The heating rate is 5-10℃ / min to 500-900℃, and the holding time is 2-4h.

8. The method for preparing a high-capacity resin-based hard carbon negative electrode material containing phosphorus and nitrogen dual doping as claimed in claim 1, characterized in that: The ball milling time in step S4 is 30-45 min.

9. A high-capacity resin-based hard carbon negative electrode material containing phosphorus and nitrogen dual doping, characterized in that: The hard carbon negative electrode material is prepared by any one of the preparation methods of claims 1-8.

10. A phosphorus-nitrogen dual-doped high-capacity resin-based hard carbon negative electrode material as claimed in claim 9, characterized in that: Application of the hard carbon negative electrode material on the graphite negative electrode of lithium ion battery.

Citation Information

Patent Citations

  • Crosslinkable flame retardant containing double DOPO and bisphthalonitrile and preparation method and application thereof

    CN113429626A

  • Composition of Phthalonitrile Resin Matrix for Polymer Composite Materials, Method for Fabrication Thereof, Method for Manufacturing of Polymer Composite Material, and Material Obtained by this Method

    US20220017712A1

Cited By

  • Preparation method and application of negative electrode material

    CN120887405A